Strategi Meningkatkan Omset UMKM melalui Pemanfaatan Sumber Daya Alam di Desa Pasi Geulima Kecamatan Teunom Kabupaten Aceh Jaya - Sari, Yulia; Diman, Banta (Lembaga Yasin AlSys, 2026)
The Kuliah Kerja Nyata (KKN) program in Desa Pasi Geulima, Teunom Subdistrict, Aceh Jaya Regency, was implemented as a community empowerment initiative aimed at optimizing local potential, enhancing human resource capacity, and strengthening village governance and environmental management. This study aims to describe the implementation and impact of the KKN program, with a focus on the development of creative economies based on local commodities, the strengthening of educational awareness, and the improvement of village governance. The core program developed was the production of Young Coconut Pudding to increase the economic value of young coconuts as a leading commodity and to open business opportunities for the community. Complementary programs included literacy and English lessons, Stop Bullying and Study Discipline campaigns in elementary schools, inter-institutional calligraphy competitions among TPA, gotong royong activities at the mosque, TPA, and PAUD, the establishment of simple gardens, the installation of gateway signs and signage for village officials’ houses, house numbering, the preparation of a village layout or map, and product marketing training for members of the PKK. The results show that the KKN program contributed positively to improving community skills, children’s educational awareness, the orderliness of administrative records and village spatial arrangements, and the growth of community initiatives in developing UMKM. The study concludes that well-directed collaboration between university students and the community can drive sustainable social change aligned with the village’s real needs, while simultaneously strengthening local capacity for the autonomous management of economic and social potential.